2016
DOI: 10.21315/jcdc2016.21.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Confirmatory Strategic Information Technology Implementation for Building Information Modelling Adoption Model

Abstract: Information technology (IT) developments in the construction industry require a proportionate response by construction professionals. Building information modelling (BIM) requires strategic changes to the traditional ways construction is carried out. BIM adoption in Malaysia is growing because of recent efforts to sensitise construction professionals on the need for strategic IT implementation. This paper builds on the theory of business process reengineering and computer integrated construction for a BIM adop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…BIM-adoption models at the user level have become prominent since 2014. Studies have been conducted in China (Ding et al 2015), India (Ahuja et al 2016, South Korea (Kim et al 2016;Park et al 2019), United Kingdom (Howard et al 2017), Australia (Sargent et al 2012), Thailand (Ngowtanasawan 2017), Malaysia (Enegbuma et al 2016), and the United States (Lee and Yu 2016).…”
Section: User-level Adoption Modelsmentioning
confidence: 99%
“…BIM-adoption models at the user level have become prominent since 2014. Studies have been conducted in China (Ding et al 2015), India (Ahuja et al 2016, South Korea (Kim et al 2016;Park et al 2019), United Kingdom (Howard et al 2017), Australia (Sargent et al 2012), Thailand (Ngowtanasawan 2017), Malaysia (Enegbuma et al 2016), and the United States (Lee and Yu 2016).…”
Section: User-level Adoption Modelsmentioning
confidence: 99%
“…Technology is one of the three major aspects of the TOE theory which focuses on the external and internal technological advancements in organizations, and the disadvantages associated with adapting new technology in different organizational structures [14,22]. Prior studies revealed that drivers such as Relative Advantage, Compatibility, and Complexity of the BIM technology to be adopted are grouped under the technological aspects of the BIM adoption model [10,28]. e hypothesis formulated about the effect of technology in different adoption stages is shown in Table 2.…”
Section: Development Of the Model Hypothesismentioning
confidence: 99%
“…The sixth model is the BIM adoption model (Enegbuma et al, 2016), which focuses on the mediating effect of collaboration on BIM adoption. It also assesses the connections between business process changes experienced in the construction industry.…”
Section: Research Backgroundmentioning
confidence: 99%